Influence of different diagnostic criteria on gestational diabetes mellitus incidence and medical expenditures in China - He, Zonglin; Xie, Huatao; Liang, Shangqiang; Tang, Yuan; Ding, Wenjing; Wu, Yanxin; Ming, Wai‐kit (Journal of diabetes investigation, 2019)
Aims/Introduction To summarize the development of the criteria for diagnosing gestational diabetes mellitus (GDM) in China, and investigate how different GDM diagnostic criteria influence the national prevalence of GDM, the national health system and the economic burden of GDM in China. Materials and Methods Retrospectively using data from women undergoing a 2‐h, 75‐g oral glucose tolerance test at 24–28 gestational weeks in the First Affiliated Hospital of Jinan University (Guangzhou, Guangdong, China) from January 2011 to December 2017, the prevalence rate of GDM and its impacts on the national health system were evaluated using different criteria (the 7th edition textbook criteria, National Diabetes Data Group 1979, World Health Organization 1985, European Association for the Study of Diabetes 1996, Japan 2002, American Diabetes Association [ADA] 2011 [International Association of the Diabetes and Pregnancy Study Groups], and National Institute for Heath and Care Excellence 2015). Results The incidence rates of GDM based on the ADA 2011 and National Institute for Heath and Care Excellence 2015 were, respectively, 22.94% (P < 0.01) and 21.72% (P < 0.01), over threefold higher than implementing the 7th edition textbook criteria (P < 0.001). On the contrary, the incidence rates of GDM diagnosed with the National Diabetes Data Group 1979 and World Health Organization 1985 guidelines were significantly less than the 7th edition textbook criteria (P < 0.001). From 2001 to 2016, the estimated national cost of treating GDM rose from ¥3.9 billion to ¥27.4 billion after implementing the ADA 2011 guidelines. Conclusions With the implementation of ADA 2011 (International Association of the Diabetes and Pregnancy Study Groups) guidelines, there are fewer adverse perinatal outcomes and cases of type 2 diabetes mellitus in the long term, but the medical costs increased significantly, and the cost‐effectiveness of diagnostic criteria in China is still yet to be confirmed. A retrospective research on 12324 singleton pregnant in China to investigate the influence on the prevalence of GDM and the economic burden of applying new diagnostic guidelines.